Penerapan Metode Simple Additive Weighting Pada Sistem Pendukung Keputusan Pengangkatan Karyawan Berbasis Web - Siti Ernawati; Risa Wati (JURNAL TEKNIK KOMPUTER, 2019)
The success or failure of a company depends on the human resources in the company. The quality of every human resource is needed to improve performance productivity. The process of appointing permanent employees is something that is often done by companies, one of the reasons is the company's appreciation of employee performance. For this reason, the process of appointing employees is more professional, so a decision support system is needed to assist in selecting employees who deserve to be appointed as permanent employees. The method will be applied in this research is simple additive weighting (SAW). SAW method is selected because it is very simple, can determine the value of weight then determine the ranking of the results of normalization. There are ten criteria and weights for each of the criteria used in this research. The purpose of this research is to design and create a web based information system as a tool for decision making in the process of appointment employees. It is hoped that this information system will benefit for the company so hat the employee appointment process do optimally and the time is more efficient.